The Diversity of Household Assets Holdings in the United States in 2007 and 2009: Measurement and Determinants - Eva Sierminska; Jacques Silber (Institute of Labor Economics (IZA), 2019)
We apply diversity indices, such as the Gini-Simpson index and entropy related indices, to the study of the distribution of individual asset holdings in the United States in 2007 and 2009. We examine the impact of the 2008 recession on asset diversity and the way individual socio-economic characteristics as well as important life events affect this measure. The focus of our analysis is on financial assets. We use a unique panel data set that provides us with comprehensive household level data for 2007 and 2009 in the United States – the Survey of Consumer Finances. We find that asset diversity increases between 2007 and 2009. In addition, it increases with age, education and income and it is lower at the bottom of the wealth distribution. Life changing situations such as getting divorced or losing one's job have a statistically significant negative effect on a change in diversity, while getting married or having deteriorating health have a positive effect. Active money management also affects asset diversity positively.
Keywords: D14; 330; diversity; financial assets; Great Recession; United States; wealth